Reactive oxygen species associated immunoregulation post influenza virus infection - Lan Wang; Zheng Cao; Zi Wang; Jimin Guo; Jing Wen (2022)
An appropriate level of reactive oxygen species (ROS) is necessary for cell proliferation, signaling transduction, and apoptosis due to their highly reactive character. ROS are generated through multiple metabolic pathways under a fine-tuned control between oxidant and antioxidant signaling. A growing number of evidence has proved their highly relevant role in modulating inflammation during influenza virus infection. As a network of biological process for protecting organism from invasion of pathogens, immune system can react and fight back through either innate immune system or adaptive immune system, or both. Herein, we provide a review about the mechanisms of ROS generation when encounter influenza virus infection, and how the imbalanced level of ROS influences the replication of virus. We also summarize the pathways used by both the innate and adaptive immune system to sense and attack the invaded virus and abnormal levels of ROS. We further review the limitation of current strategies and discuss the direction of future work.